2014
DOI: 10.1371/journal.pone.0111521
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and Neuromuscular Responses to Mechanical Vibration Applied to Upper Extremity Muscles

Abstract: ObjectiveTo investigate the acute residual hormonal and neuromuscular responses exhibited following a single session of mechanical vibration applied to the upper extremities among different acceleration loads.MethodsThirty male students were randomly assigned to a high vibration group (HVG), a low vibration group (LVG), or a control group (CG). A randomized double-blind, controlled-parallel study design was employed. The measurements and interventions were performed at the Laboratory of Biomechanics of the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 44 publications
(67 reference statements)
3
36
0
1
Order By: Relevance
“…In contrast, Giminiani et al (2014) showed no significant difference on handgrip strength. Thirty male students were randomly assigned to a high vibration group (HVG), a low vibration group (LVG), or a control group (CG) and were exposed to a series of 20 trials 10 s of synchronous WBV with a 10-s pause between each trial and a 4-min pause after the first 10 trials.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…In contrast, Giminiani et al (2014) showed no significant difference on handgrip strength. Thirty male students were randomly assigned to a high vibration group (HVG), a low vibration group (LVG), or a control group (CG) and were exposed to a series of 20 trials 10 s of synchronous WBV with a 10-s pause between each trial and a 4-min pause after the first 10 trials.…”
Section: Resultsmentioning
confidence: 59%
“…Studies have also described important effects of vibration exposure on upper body muscular activity, as an increase in skeletal muscle activity in the arms (Marín et al, 2015;Marín et al, 2011;Marín et al, 2013) and on the handgrip strength (Giminiani et al, 2014;Kurt et al, 2015) .…”
Section: Introductionmentioning
confidence: 99%
“…It exerts biological effects throughout a man's entire life (Ohl and Quallich, 2006). Concerning the effect of the WBV exercise in the plasma level of testosterone, Bosco et al, 2000;Santos-Filho et al, 2011;Nanemi, 2012 andDi Giminiani et al, 2014 have reported significant increase in testosterone levels in response to these exercises. However, other authors have not found increase in the concentration of testosterone due to WBV exposure (Cardinale et al, 2006;Erskine et al, 2007).…”
Section: Hormonal Responses To Wbvmentioning
confidence: 99%
“…In addition, WBV exercises have been considered as a noninvasive and non-pharmacological intervention [19]. The effects of WBV exercises on plasma concentrations of selected biomarkers have been studied in human beings [20][21][22]. In addition, some investigations have reported that WBV exercises could improve muscle activity, force and power [23,24], balance and flexibility [25], and cognitive performance [26].…”
Section: Introductionmentioning
confidence: 99%